Особливості ідентифікації ризиків ринку Big Data - Шандрівська, О. Є.; Кириленко, А. А.; Shandrivska, O. Ye.; Kyrylenko, A. A. (Видавництво Львівської політехніки, 2021)
Досліджено стан та тенденції розвитку глобального ринку Big data. Проаналізовано динаміку місткості глобального ринку Big Data за 2011–2020 рр. та ідентифіковано основні сегменти цього ринку за джерелами доходу, проаналізовано динаміку доходів п’ятірки лідерів країн глобального ринку Big data. Окрему увагу зосереджено на аналізуванні цільового сегмента персональних даних осіб. Для аналізування глобального ринку Big Data застосовано концепцію п’яти сил конкуренції за М. Портером та виконано SWOT-аналіз глобального ринку Big Data із виокремленням стратегічних напрямів розвитку для комбінацій сильних і слабких сторін функціонування ринку Big Data, а також загроз та можливостей впливу на нього чинників зовнішнього середовища. Ідентифіковано основні ризики та організаційні процедури щодо запобігання їм у діяльності підприємств на глобальному ринку Big Data, здійснено оцінювання ризику витоку даних внаслідок кібератак.

The paper hypothesizes that the dynamic digitalization of the economy, based on the benefits of using Big data, accelerates the use in management and production processes of technologies offered by this market. However, it is noted that the acquisitions of the Big data market also exacerbate the socio-economic contradictions between countries with developed market economies and institutionally underdeveloped countries, which include Ukraine. The authors of the study proposed to identify the Big data market with such key indicators as total revenue, number of Internet users, losses of Big Data market participants from data leakage. Thus, the high rates of development of the Big data market in terms of growth of total market income in 8,03 times during 2011–2020 were witnessed. The main segments of the Big Data market (service segment, software segment and service segment) were identified. It is established that the largest share of the Big Data market is occupied by the services segment (37,5 % in 2020). From 2021, the growth rate of the software segment is expected to exceed other segments of this market – hardware and services. The results of the analysis of the Big Data market by M. Porter's five forces model show that the most important of the competitive forces in the market is a high level of competition, in which market participants are encouraged to focus on potential needs and expectations of their customers to strengthen bases of differentiation and clear positioning of the services. According to the results of the SWOT-analysis of the Big Data market, the following strengths were identified: business expansion due to the increase in the amount of information it owns; increasing the number of customer reviews through social networks; establishing strategic partnerships with suppliers, dealers and other stakeholders through the use of Big Data; permanent training of employees to maintain the competitiveness of organizations; established IT system of the enterprise, which promotes faster adoption of effective management decisions; high incomes due to effective management decisions, possession of market research results through Big Data technologies. The identified market opportunities are: population growth, which means an increase in the number of potential consumers and the amount of data collected; growth in the number of enterprises that implement e-commerce in their activities; growth of active consumers due to the integration of Big Data into social networks; increasing the share of automated processes, which helps reduce costs; growing popularity of IT specialization in universities; globalization of the economy, which allows companies to expand their activities to other countries. On the basis of identified strengths of the market and its capabilities, the following strategic directions of development are proposed: entry of enterprises into new markets due to market globalization and effective implementation of Big Data technologies; use of social networks to collect consumer data and involve them in Big Data processes; improvement of the e-commerce system of enterprises due to the capabilities of well-established IT systems of the enterprise with the capabilities of Big Data; reduction of product prices due to cost optimization and effective interaction with contractors. The results of the research allowed to identify the following main risks of the industry: destruction of data confidentiality; collection of false data, infringement of intellectual property of a third party, etc. The formed risk matrix indicates that the most significant risks of this market are the reduction of information security of the entity due to hacker attacks (probability of 50 %, significant damage) and the destruction of data confidentiality (probability of 25 %, significant damage). Qualitative interpretation of risks in the Big Data market allowed to characterize the impact of adverse factors of internal and external environments, namely: insufficient unreliability of cloud storage for data storage; high level of distrust of data carriers to companies using Big Data; high staff turnover in the market, etc. Assessing the risk of data loss due to hacker attacks allowed to identify it as a risk of a high level of importance (6 p.). Based on the obtained result, it is concluded that the activities of Big Data market participants are vulnerable to possible hacker intrusions and require more effective measures to ensure reliable data protection of enterprises and their customers.
Features of Big Data market risk identification
Keywords: глобальні дані; ринок Big data; інтернет речей; цифровізація економіки; концепція п’яти сил конкуренції Портера; SWOT-аналіз; ризики; global information; Big data market; Internet networks; digitalization of the economy; the concept of development of Porter’s competitive forces; SWOT-analysis; risks; 004.67; 339.138